Anion-dependent ion-pairing assemblies of triazatriangulenium cation that interferes with stacking structures - Haketa, Yohei; Matsuda, Takuma; Maeda, Hiromitsu (Beilstein Journal of Organic Chemistry, 2024)
Ion pairs of N-(2,6-dimethylphenyl)-substituted triazatriangulenium (TATA+) cation with various counteranions were synthesized to investigate the interactions for the bulky cation. Single-crystal X-ray analysis of the TATA+ ion pairs revealed solid-state ion-pairing assemblies without stacking at the cationic π-planes. The TATA+ cation showed counteranion-dependent assembly structures, with smaller counteranions located at the top of TATA+ and bulkier counteranions displaced from the TATA+ plane to interact with the surrounding TATA+.
Keywords: charged π-electronic systems; ion pairs; single-crystal X-ray analysis; solid-state assemblies; triazatriangulenium cation